The Use of Ultrasound to Exclude Extremity Fractures in Adults. Issue 3 (28th September 2017) - Døssing, Kaj; Mechlenburg, Inger; Hansen, Lars Bolvig; Søballe, Kjeld; Østergaard, Helle
Abstract : Background: The purpose of the present study was to investigate whether ultrasonography can be used as a diagnostic tool to exclude extremity fractures in adults. Methods: This prospective comparative study involved 91 patients (age, ≥18 years) who had been referred by general practitioners for a conventional radiographic examination of a suspected extremity fracture. No additional clinical examination was performed. Ultrasound examination was consistently carried out prior to conventional radiographic examination, which was regarded as the gold standard. At the end of the study, the positive scans were confirmed by a specialist who was highly skilled in ultrasonography. Results: The prevalence of fractures in the study population was 27%. Ultrasonography had a sensitivity of 92%, a specificity of 94%, a positive predictive value of 85%, a negative predictive value of 97%, a positive likelihood ratio of 15.33, and a negative likelihood ratio of 0.085. There seemed to be no association between the anomalous results and patient age or the specific anatomical region of the fracture. Conclusions: The present study indicates that ultrasonography, when performed and interpreted by experienced ultrasonographers, has high accuracy for the diagnosis of a suspected extremity fracture. No systematic differences were found between the results of radiography and ultrasonography, and ultrasonography showed a high sensitivity and specificity. Level of Evidence: DiagnosticLevel II . See Instructions for Authors for a complete description of levels of evidence.